Does primary immunisation status predict MMR uptake?. Issue 1 (7th May 2008) - Pearce, A; Elliman, D; Law, C; Bedford, H
Abstract : Objective: To investigate the relationship between primary immunisation status and MMR uptake. Design: Nationally representative Millennium Cohort Study. Setting: Children born in the UK, 2000–2002. Participants: 14 578 children with immunisation data. Main outcome measures: MMR status at 3 years, defined as immunised with MMR, immunised with at least one single antigen vaccine or unimmunised. Results: 88.6% of children had been immunised with MMR, 5.2% had received at least one of the single antigen vaccines and 6.1% were unimmunised against measles, mumps and rubella at age 3 years. Children who were unimmunised with the primary vaccines at ages 9 months (1.2%, n = 168) and 3 years (0.4%, n = 67) were 13 (95% CI 10.8 to 14.7) and 17 (95% CI 14.6 to 19.7) times more likely to be unimmunised against measles, mumps and rubella compared with children who were fully immunised. They were also more likely to be immunised with at least one of the single antigen vaccines with risk ratios of 2.8 (95% 1.2 to 6.1) and 4.3 (95% CI 1.8 to 10.1). Similar but smaller associations were observed if children were partially immunised with the primary vaccines at 9 months (3.4%, n = 502) and 3 years (3.6%, n = 522) with risk ratios of 4.0 (95% 3.2 to 4.9) and 5.2 (95% 4.2 to 6.1) for no MMR immunisation, and 2.0 (95% C 1.1 to 3.6) and 1.6 (95% CI 1.1 to 2.5) for single antigen vaccine use. Conclusion: Children who remain unimmunised with primary vaccines are also more likely not to receive MMR. More work is needed to determine how best to target this group.